Portret intelektualisty w „Dziennikach" Raymonda Queneau - Lubas-Bartoszyńska, Regina (Przestrzenie Teorii, 2007)
The intellectual portrait in R. Queneau's "Diaries" is built by the author himself and - to the same extent - by the reader, on the basis of the way in which the records are organized and their contents. Although the autobiographical speaker in the "Diaries" adopts many models of self-presentation (e.g. as an intimist, a traveller, a patriot, a humanitarian), one of them, that of an intellectual, encyclopaedist, erudite, writer and philosopher, pervades all the others; playing with them is one of the methods of presenting oneself as an intellectual, besides direct reference, biography, thematics, and artistic programmes.